Revealing the Invisible Emotion Work of Caregivers: A Photovoice Exploration of Informal Care Provided by Family Caregivers for Post-9/11 Veterans With Traumatic Brain Injuries. Issue 1 (January 2021) - Abraham, Traci H.; Ono, Sarah S.; Moriarty, Helene; Winter, Laraine; Bender, Ryan E.; Facundo, Ray; True, Gala
Abstract : Objective: Describe the different forms of emotion work performed by family caregivers of veterans living with a traumatic brain injury (TBI). Design: Collaborators were provided cameras to take photographs illustrating their experiences as family caregivers. The meaning behind caregiver photographs was solicited using photoelicitation interviews and coded. Setting: Homes of veterans or other informal settings in 2 regions of the United States served by the Southeast Louisiana Veterans Health Care System and the Veterans Affairs Portland Health Care System. Participants: Twenty-six family caregivers of post-9/11 era veterans with TBI. Results: Caregivers described performing different types of intangible, and largely invisible, work centered on emotion management. Emotion work primarily involved creating a new normal, keeping things calm, and suppressing their own emotional experiences to "put on a brave face." Although having derived a sense of satisfaction and identity from their role, caregivers acknowledged that emotion work was challenging and sometimes stressful. The Photovoice method allowed caregivers to express through metaphor experiences that otherwise would have been hard to articulate and share with others. Conclusion: Findings signal a need for healthcare systems and providers to acknowledge emotion work as a potential source of stress and to provide multifaceted support for veterans and family caregivers.